Studi Komparatif Unsur-Unsur Budaya Chika Idol di Jepang dan Indonesia - Hidayati, Nur; Furisari, Pipiet (Vocational College of Diponegoro University, 2026)
J-pop culture has greatly influenced Japanese culture, including the emergence of Chika Idols (地下アイドル). Chika Idols are independently managed idols who usually perform in small venues. They are also known as concert idols or indie idols. The purpose of this study is to identify the differences and similarities between the influence of Chika Idol culture in Japan and Indonesia. This study uses a qualitative method with comparative methodology. The objective is to explore the differences and similarities between Japanese and Indonesian Chika Idol culture. The data used were observations at the KirinFes Bandung event, Semilir Japan Matsuri 4 in Semarang, and Toys and Hobbies in Surabaya. Secondary data was obtained from YouTube accounts such as 【ヲタ芸】白狐-Hako, websites related to the world of Chika Idol such as FUN!JAPAN, Japan Times, J-Wave, Media Factory, YumeTwins, and Yes Tiger, as well as several journals related to Chika Idol. The research findings reveal four types of activities that exhibit both differences and similarities in the Japanese Chika Idol culture in Indonesia. The conclusion is that the differences and similarities in the influence of Japanese Chika Idol culture in Indonesia are significant, leading many people to desire their own idol group.